Testing the Teman Ternak Website Using Black Box Testing with the Equivalence Partitioning Method - Dermawan, Rival Fitrah; Radiansyah, Fahri; Aslam, Anargya Rabbani; Fadillah, Muhamad Mauladi; Wicaksono, Aditya; Mindara, Gema Parasti (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
Software testing is a crucial stage in the development cycle to ensure program functionality runs as expected and maintains good quality. This process aims to identify errors so they can be fixed before the software is released to users. One of the software objects of this research is the Teman Ternak website. Teman Ternak is a website-based digital platform that functions as telemedicine, designed to overcome distance and time barriers between farmers and veterinarians, providing a platform that allows farmers to obtain remote consultation services, including initial diagnosis and treatment for diseases affecting their livestock. Testing on this website was conducted using the Black Box Testing method by applying the Equivalence Partitions technique. The Black Box method is used to test website functionality from a user perspective without needing to know the internal code structure. Meanwhile, the Equivalence Partitions technique is a testing technique that focuses on designing test cases by grouping input data on each form on the Teman Ternak website. Input data is grouped into test classes (test cases) with expected results of valid or invalid values. The purpose of testing on the Teman Ternak website is to detect and minimize functional failures during implementation, so that errors found can be fixed more quickly and the website quality improves.